Ultraviolet Radiation Emissions and Illuminance in Different Brands of Compact Fluorescent Lamps - Shahram Safari; Sina Eshraghi Dehkordy; Meghdad Kazemi; Habibollah Dehghan; Behzad Mahaki (International Journal of Photoenergy)
Introduction. Replacing incandescent lamps with compact fluorescent lamps (CFLs), which are three to six times more efficient, is one of the easiest methods to achieve energy efficiency. The present study aimed to evaluate relationships between UV emissions radiated and illuminance CFLs. Material and Methods. This pilot study was conducted on 16 single envelope CFLs. The illuminance and UV irradiance of various types of CFLs are measured on a three-meter long optical bench, using a calibrated lux meter and UV meter, and measurement was done in 10, 25, 50, 100, 150, and 200 cm, in three angles, including 0°, 45°, and 90°, at the ages of 0, 100, and 2000 hours. Result. UVC irradiance was not observed at the distance of 10 cm in all of lamps. The lowest value of UVB irradiance was recorded in Pars Khazar lamp, while the highest value was recorded in Etehad lamps. UVR values measured at different times showed negligible differences; the highest asset value was detected in zero times. One way ANOVA indicated that relationships between UVA irradiance and illuminance were significant (P<0.05). Conclusion. UVB irradiance in most of the lamp in 10 and 25 cm was more than occupational exposure and UVA except for the fact that Pars Khazar 60 watts and Nama Noor 60 watts were less than occupational exposure.